Dieta de golfinhos e sobreposição trófica com a pesca de arrasto na costa central do Brasil - Rupil, Gabriel Martín (2016)
In order to explore the extent of trophic niche overlap between dolphins and trawling fishery in Brazilian central coast, dolphins’ feeding habits were characterized and fish composition of trawls in Conceiçao da Barra was estimated. Diet of three species of dolphins was investigated by means of stomach content analysis. Fifty-four Sotalia guianensis, 18 Pontoporia blainvillei and one Tursiops truncatus stomach content sample were analyzed. Fish composition was estimates from a 45 trawls sampling carried out through May 2014 to July 2015. Regarding to trophic overlap estimation, fish composition differentiation was tested and analyzed through multivariate analysis. The degree of trophic overlap among groups was estimated and pairwise comparison was made using Horn´s overlap index. A description of several ecological patterns was made by trophic networks modeling tools. Regarding to Sotalia guianensis diet, squids were observed to be the most frequent type of prey consumed, as Isopisthus parvipinnis showed the second largest frequency of occurrence. Yet, Isopisthus parvipinnis was the most frequent prey consumed by Pontoporia blainvillei. Centropomus spp. was the largest identified item counted for the single Tursiops truncatus sample examined. The Scianidae family features the largest count of individuals for all groups assessed in this study. New registers of preys are presented. This study represents the first description on Pontoporia blainvillei feeding habits carried out in the northern Espirito Santo state coast. As a result, hereby I conclude that Pontoporia blainvillei is the most vulnerable dolphin species to keep on the effects of potential consuntive competition and that Isopisthus parvipinnis stocks are likely to decline dramatically by overfishing in this theses´ area of study.